Hypertrophic Pisiform: A Case of Osteoid Osteoma - Hori, Keiko; Nakamura, Toshiyasu; Sato, Kazuki; Ikegami, Hiroyasu; Toyama, Yoshiaki (Journal of Wrist Surgery, 2020)
We treated an extremely rare case of osteoid osteoma of the pisiform. Pisiform hypertrophy caused persistent pain and ulnar nerve irritation at Guyon's canal after the initial trauma. The re-enlargement of the pisiform attracted our attention allowing us to ultimately diagnose the condition as osteoid osteoma and treat the patient with a successful clinical result.
Keywords: osteoid osteoma; pisiform; hypertrophic change